Customer Relationship Management Strategy at PT POS Indonesia (Persero) Ngawi Branch Office - Julianti, Kiptiana Dwi; Subiyantoro (Politeknik Negeri Madiun, 2023)
Managing good relationships with customers can be applied to a concept known as Customer Relationship Management (CRM). The implementation CRM allows companies to personalize interactions with customers. Based on available information, companies can provide specific and personalized services to each customer. Improving service quality makes customers feel valued and important, this will increase customer loyalty. The purpose of this study was to determine and describe the application of Customer Relationship Management strategies in the field of Corporate Courier and Logistics at PT Pos Indonesia (Persero) Ngawi Branch Office. The research was conducted using descriptive qualitative methods with data collection through interviews and documentation. Data processing techniques are carried out with data exposure and discussion. The results of the research show that the implementation of CRM strategies at the Ngawi Branch Post Office is carried out in seven stages. In the first stage, one-to-one marketing, customer IDs are made and interact personally. Then conduct employee training, provide complaint services, and conduct promotions. Furthermore, in addition to conducting routine visits and marketing directly or through social media, it also conducts free pick-up services. The last stage is to make the process continuous.